That syncing feeling: Early user experiences with the cloud - Marshall, Cathy; Tang, John (Designing Interactive Systems (DIS) 2012, 2012)
We studied how people use file sync and sharing services to better understand how early adopters conceptualize their interactions with the cloud. A survey of 106 users provided background information about current use of these cloud storage services and identified 19 people for in-depth interviews. Use cases described in the interviews revealed a hierarchy of concepts that participants needed to master to make full use of these services. Five pivotal concepts demonstrate that users make sense of the cloud as a: personal file repository, shared file repository, personal replicated file store, shared replicated file store, and synchronization mechanism that coordinates among replicas. We propose specific ways in which process transparency and interface scaffolding can help users build a more robust model of cloud services.